Behavioral and sociodemographic correlates of the body mass index in Brazilian workers - Priscila Cristina Santos; Kelly Samara da Silva; Bruno Gonçalves Galdino da Costa; Gabrielli Thais de Mello; Elusa Santina Antunes de Oliveira; Markus Vinícius Nahas (Revista Brasileira de Atividade Física e Saúde)
An unhealthy body composition has been linked with chronic diseases and premature deaths that could be prevented. It is desirable to understand how modifiable behaviors are linked to the body composition of industrial workers, and identify risk groups among the population to plan interventions and policies. The aim of the study was to identify the sociodemographic, physical activity, sedentary behavior, and nutritional correlates of the body mass index (BMI) of Brazilian industrial workers. Data were used from the “Lifestyle and Leisure Habits of Industrial Workers” study (n = 45,508), conducted between 2006 and 2008, in 24 of the 27 Brazilian states. Gender, physical activity practice, television viewing, consumption of sweetened drinks, weight, and height were reported by the participants, and BMI was calculated. Linear regression analysis was conducted to identify the factors associated with BMI. Women had a lower BMI when compared to men (-1.63 kg/m2, CI95%: -1.71; -1.56). Age and television viewing were positively associated with BMI and physically inactive adults had a BMI of 0.22 kg/m2 (CI95%: 0.15; 0.29) greater than those who were active during leisure time. There was no association between BMI and sweetened drink consumption. Usually, BMI is higher among men, older individuals, those who watch more hours of TV daily, and those who do not practice physical activity during leisure time. When possible, it is suggested to promote the practice the practice of physical activity during leisure time without directing actions to comply with the recommendation of 150 minutes per week with the understanding that some activity is better than none, as well as stimulate the reduction of TV viewing time among workers.